A study of some morphological Properties of Laurus nobilis L, which is naturally distributed in different locations in Syria (Journal of Hama University, 2024)
The study was conducted during 2019-2020 at various geographic locations in Syria, in the provinces of Latakia (Kasab) and Hama (Al-Ghab), comprising a total of 15 sites. The aim of the study was to investigate some morphological characteristics of the fruits and seeds of Laurus nobilis L. in his natural habitats of Kasab and Al-Ghab. The fruits and seeds of Laurus nobilis individuals in the studied sites showed significant differences in the morphological characteristics , with the individual GH2 from site Al-Ghab2 which showed significant superiority over the other individuals in terms of fruit length (1.65 cm) and fruit diameter (1cm). Furthermore, the studied individuals, which belong to different geographic locations, showed no Morphological differences, with an estimated Morphological similarity ranging from 0.95 to 0.97.